PENDIDIKAN KARAKTER DAN KETELADANAN GURU DALAM KEPRIBADIAN SISWA - Eka Novia Nisa (QATHRUNÂ, 2021)
The purpose of this study is 1) To find out the character education given by the teacher in fostering student personality 2) To find out the teacher's example by instilling moral values ​​in student personality development 3) To find out the supporting and inhibiting factors for providing guidance and guidance morals to students and supporting and inhibiting factors for providing moral guidance and guidance to students and 4) To find out the comparison of how to instill PAI teachers in the personality development of students at MTs al Ghifari Karangtanjung and MTs Al Bina Cadasari Pandeglang. This research method is a qualitative approach. The research time is about 4 months, taking place at MTs al Ghifari Karangtanjung and MTs Al Bina Cadasari Pandeglang. In collecting information from informants, both written and verbal, the researchers collected data by means of observation, in-depth interviews with 14 informants consisting of 2 madrasah principals, 6 teachers and 6 students, as well as documentation, then analyzed and processed using techniques. reduction, presenting data as well as verifying so that it can refer to the research objectives in question. The results of the study, 1) the character education provided by the teacher in fostering the personality of students through learning by familiarizing the attitude and example of the Prophet Muhammad; 2) exemplary teachers by instilling moral values ​​in the personality development of students at MTs al Ghifari Karangtanjung and MTs Al Bina Cadasari Pandeglang through discipline and responsibility both in the process and outside of learning; 3) To find out the supporting and inhibiting factors in providing moral guidance and guidance to students, it is done by preparing conditions that allow the formation of individual and social piety; 4) To find out the comparison of how to instill PAI teachers in the personality development of students at MTs al Ghifari Karangtanjung and MTs Al Bina Cadasari Pandeglang through positive activities to help students facilitate the learning process towards success.